The Financial crises of the third millennium and their impact on the performance of the global tourism sector - سلطان جاسم النصراوي (Iraqi Journal for Administrative Sciences, 2024)
Over the past decade, the global economy has witnessed severe economic turmoil, the global financial crisis (the subprime crisis) that began in the end of 2007, moving from the United States of America to the effects of most of the world, and the world economy suffered greatly. Itis stalemate until fell again in a powerful crisis shook the European Union and almost led it in to collapse and disintegration. These crises have been reflected in the overall activities and sectors of the economy. Economic growth has declined, unemployment rates have risen, financial markets have experienced violent fluctuations in their indices, capital has fled, investments have declined, global trade has slowed and the world economy has fallen into deep and prolonged recession. The tourism sector, one of the fastest growing sectors and a dynamic engine for development, economic growth, job creation and a source of foreign exchange savings, was affected by the repercussions of these crises. Foreign revenues decreased, employment decreased and tourist numbers declined. The crises. To prove the tourism sector vulnerability to economic crises, on the other hand, it is clear that tourism has the ability to cope with those fluctuations and the speed to recover from those risks.